Protein Expression of the Microglial Marker Tmem119 Decreases in Association With Morphological Changes and Location in a Mouse Model of Traumatic Brain Injury - Mercurio, Domenico; Fumagalli, Stefano; Schafer, Martin K-H; Pedragosa, Jordi; Ngassam, Lionel Dejeumen Claude; Wilhelmi, Verena; Winterberg, Sarah; Planas, Anna M.; Weihe, Eberhard; De Simoni, Maria-Grazia (Frontiers in Cellular Neuroscience, 2022)
The activation of microglia and the infiltration of macrophages are hallmarks of neuroinflammation after acute brain injuries, including traumatic brain injury (TBI). The two myeloid populations share many features in the post-injury inflammatory response, thus being antigenically indistinguishable. Recently Tmem119, a type I transmembrane protein specifically expressed by microglia under physiological conditions, was proposed as a tool to differentiate resident microglia from blood-borne macrophages, not expressing it. However, the validity of Tmem119 as a specific marker of resident microglia in the context of acute brain injury, where microglia are activated and macrophages recruited, needs validation. Our purpose was to investigate Tmem119 expression and distribution in relation to the morphology of brain myeloid cells present in the injured area after TBI. Mice underwent sham surgery or TBI by controlled cortical impact (CCI). Brains from sham-operated or TBI mice were analyzed by in situ hybridization to identify cells expressing Tmem119, and by Western blot and quantitative immunofluorescence to measure Tmem119 protein levels in entire brain regions and single cells. The morphology of Iba1+ myeloid cells was analyzed at different times (4 and 7 days after TBI) and several distances from the contused edge in order to associate Tmem119 expression with morphological evolution of active microglia. In situ hybridization indicated increased Tmem119 RNA along with increased microglial activation in the contused area and surrounding regions. On the contrary, the biochemical evaluation showed a drop of Tmem119 protein levels in the same areas. Tmem119 immunoreactivity decreased in Iba1+ myeloid cells found in the contused cortex at both time points, with the cells showing the hypertrophic amoeboid morphology having no Tmem119 expression. Tmem119 was present on ramifications of resident microglia and its presence decreased as a consequence of microglia activation in cortical areas close to contusion. Based on the data, we conclude that the decrease of Tmem119 in reactive microglia may depend on the process of microglia activation, which involves the retracting of their branchings to acquire an ameboid shape. Tmem119 immunoreactivity decreases in reactive microglia to similar levels than blood-borne macrophages, thus failing to discriminate the two myeloid populations after TBI.